The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.24193/subbchem.2017.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro study of the different orthodontic brackets using two etching techniques

Abstract: ABSTRACT. Direct bonding of the bracket to the enamel is the elective procedure for the orthodontic treatment. Among various factors influencing the adhesive force at the enamel level, the etching technique seems to be the most important one. The present study aims at evaluating the influence of the storage media and the etching technique used, on the bond strength between different bracket types and dental structures. The results of this study showed that, regardless of the brackets and the immesion solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous research has reported various incidence rates of bracket detachment, from 28.3% to relatively low incidence values of 0.6-9.6% [9]. Other studies have also compared several techniques and materials for orthodontic bonding [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported various incidence rates of bracket detachment, from 28.3% to relatively low incidence values of 0.6-9.6% [9]. Other studies have also compared several techniques and materials for orthodontic bonding [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that the water sorption causes expansion of the adhesive material until an equilibrium value [14][15][16][17]. Another study shows that most of the hygroscopic expansion occurs in the first two weeks, with the balance achieved in about eight weeks [18].…”
Section: Resultsmentioning
confidence: 99%